The Role of Generation - Z in Implementation of the Generation Program Planning (GENRE) Going to Generation Setup Life Family - Zulkifli Siregar; Nur M Ridha Tarigan; Supar Wasesa; Ilham Sonata; M. Sahnan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research paper explores the significant role of Generation Z individuals in the successful execution of the Generation Program Planning (GENRE) and its impact on shaping the family setup and lifestyle of the future. Generation Z, born roughly between the mid-1990s and early 2010s, represents a generation that has grown up in a technologically advanced and interconnected world. As they enter adulthood and become active members of society, understanding their influence on the family structure and lifestyle choices is essential for policymakers, educators, and families themselves. The findings reveal that Generation Z plays a crucial role in the implementation of the Generation Program Planning, actively shaping the family setups and lifestyles of the future. Their unique perspectives, tech-savvy nature, and emphasis on social and environmental consciousness influence the ways families function and interact. However, the research also identifies certain barriers to successful implementation, such as traditional norms, resistance from older generations, and socioeconomic disparities.Ultimately, this study sheds light on the Generation Z cohort's impact on the Generation Program Planning and its implications for family life. Policymakers and educators can use these insights to design more effective programs that cater to the needs and values of this generation. As Generation Z continues to grow in influence, understanding their role in shaping family setups and lifestyles becomes paramount for a sustainable and thriving society.